Tingkat percaya diri dan keterampilan micro teaching - Apriani, Leni; Alpen, Joni; Arismon, Al (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The purpose of this study was to see the level of student confidence in micro teaching learning for students of Physical Education Health and Recreation, Univeritas Islam Riau. This type of research is a quantitative descriptive study. The population in this study were all students of Physical Education for Health and Recreation Semester VI of the 2019/2020 Academic Year who had completed the micro teaching course which received 211 people. The research sampling technique used total sampling. The research was conducted by applying a questionnaire to students. Based on the results of the research analysis, the findings obtained were 34.59% of self-competence results in the "sufficient" category and 35.07% of micro teaching skills in the "sufficient" category. This proves that Health and Recreation Physical Education students must be able to hone their ability to practice speaking skills so that they can become more competent prospective teachers in their fields.